Analisis Geomorfologi Daerah Pesisir Desa Biluhu Timur, Kecamatan Batudaa Pantai, Gorontalo - Mamonto, Amelia; Arifin, Yayu; Marina, Siti (Universitas Negeri Gorontalo, 2025)
This study aims to investigate the geomorphological characteristics of Biluhu Timur Village, Batudaa Pantai District, Gorontalo. The analysis was carried out using National Digital Elevation Model data, topographic maps, and spatial processing through Geographic Information Systems to produce slope-gradient maps, morphographic classifications, drainage patterns, and geomorphological units. The study area is composed of igneous rock lithologies, namely granite and dacite, as well as limestone of the wackestone type. The results show that the area exhibits an elevation range from –5 to 340 meters, forming four morphographic classes and five slope-gradient classes, dominated by very steep zones with high susceptibility to erosion and landslides. The drainage patterns identified in the area include parallel and dendritic patterns, with valley development ranging from youthful “V-shaped” forms to mature “U-shaped” forms. Based on the analysis and field validation, three principal geomorphological units were delineated: the Lava Flow Ridge Unit, the Denudational Hill Unit, and the Coastal Plain Unit. These findings provide essential baseline information for land-use planning, disaster mitigation, and sustainable regional management.